Assessment of hydraulic efficiency of inter-farm irrigation channels in the context of Field Research (Международный научный журнал «Инженер», 2026)
90-91% of the water resources in our country are focused on agriculture. More than 80% of the inter-farmirrigation channels are soil-dominated, and 30-35% of the water in these channels is lost by filtration. Studiessuggest that the useful operating coefficient of irrigation networks is on average 0.63, indicating the need toimprove the efficiency of water resource utilization. In this article, the hydraulic efficiency of the inter-farmirrigation channels located in the Tashkent region was assessed by taking natilas in field conditions. Ways wereproposed to determine water consumption in canals, calculate filtration losses, and improve efficiency.